2021
DOI: 10.2147/ott.s311907
|View full text |Cite
|
Sign up to set email alerts
|

Platelets: The Emerging Clinical Diagnostics and Therapy Selection of Cancer Liquid Biopsies

Abstract: Due to the inherent molecular heterogeneity of metastatic tumours and the dynamic evolution ability of tumour genomes, tumour tissues obtained through biopsy and other methods cannot capture all of the features of tumour genomes. A new diagnostic concept called "liquid biopsy" has received widespread attention in recent years. Liquid biopsy has changed the clinical practice of oncology and is widely used to guide targeted drug utilization, monitor disease progression and track drug resistance. The latest resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…TEPs have several clinical utilities in various cancer types apart from gastrointestinal cancers, including breast cancers ( Best et al, 2015 ; Alimirzaie et al, 2019 ; Yao et al, 2019 ; Mendoza-Almanza et al, 2020 ), nasopharyngeal cancers ( Wang et al, 2019c ), prostate cancers ( Tjon-Kon-Fat et al, 2018 ; Boerrigter et al, 2020 ), lung cancers ( Sheng et al, 2018 ; Xing et al, 2019 ), glioblastoma ( Campanella et al, 2020 ; Sol et al, 2020 ; Meng et al, 2021 ), and ovarian cancer ( Mysona et al, 2019 ; El-Arabey et al, 2020 ). Most studies evaluating the role of TEPs have qualitatively reported the RNA profiles of TEPs, whereas the protein profiles of TEPs still remain considerably unexplored.…”
Section: Tumor-educated Plateletsmentioning
confidence: 99%
“…TEPs have several clinical utilities in various cancer types apart from gastrointestinal cancers, including breast cancers ( Best et al, 2015 ; Alimirzaie et al, 2019 ; Yao et al, 2019 ; Mendoza-Almanza et al, 2020 ), nasopharyngeal cancers ( Wang et al, 2019c ), prostate cancers ( Tjon-Kon-Fat et al, 2018 ; Boerrigter et al, 2020 ), lung cancers ( Sheng et al, 2018 ; Xing et al, 2019 ), glioblastoma ( Campanella et al, 2020 ; Sol et al, 2020 ; Meng et al, 2021 ), and ovarian cancer ( Mysona et al, 2019 ; El-Arabey et al, 2020 ). Most studies evaluating the role of TEPs have qualitatively reported the RNA profiles of TEPs, whereas the protein profiles of TEPs still remain considerably unexplored.…”
Section: Tumor-educated Plateletsmentioning
confidence: 99%
“… 38 In the presence of occult cancer, platelet generation can be severely augmented following numerous tumor-derived and systemic factors. 36 , 39 High TPC has been documented in various cancers 40 ; this high TPC is related to systemic inflammation, 41 and increased potential risk of tumor progression in CRC. 42 Thrombocytosis in adults older than 40 years could be an indicator of cancer 43 and nearly 40% of cases with unknown thrombocytosis (i.e.…”
Section: Cancer and Plateletsmentioning
confidence: 99%
“…Neoplastic cells can relocate molecules such as RNA to platelets via direct connection and delivery of exosomes, which is able to modify the platelet precursor RNA, and under the effect of neoplastic cells and neoplastic milieu platelet immature mRNA is transformed into mature RNA able to form functional proteins, generating TEPs ( Figure 2 ). The identification of TEPs in the peripheral blood of neoplastic subjects is awaiting employment in the tumour diagnosis [ 134 , 135 , 136 ] ( Table 3 ).…”
Section: Tumor-educated Platelets (Tep) and Liquid Biopsymentioning
confidence: 99%